2020
DOI: 10.1136/jitc-2019-000462
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction by thiostrepton improves the efficacy of immunogenic chemotherapy

Abstract: BackgroundImmunogenic cell death (ICD) is a peculiar modality of cellular demise that elicits adaptive immune responses and triggers T cell-dependent immunity.MethodsFluorescent biosensors were employed for an unbiased drug screen approach aiming at the identification of ICD enhancers.ResultsHere, we discovered thiostrepton as an enhancer of ICD able to boost chemotherapy-induced ATP release, calreticulin exposure and high-mobility group box 1 exodus. Moreover, thiostrepton enhanced anticancer immune responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 36 publications
2
31
0
1
Order By: Relevance
“…29 Autophagy induction in cancer cells is required for the induction of immunogenic cell death (ICD) by OXA 30 or the combination of CDDP +crizotinib, 20 meaning that cancer cells in which Atg5 expression has been suppressed do not respond to these combination regimens in vivo. 20,30,31 Hence, the fact that HCQ fails to interfere with the efficacy of ICD-based therapeutic regimens might be explained by its incapacity to fully block autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…29 Autophagy induction in cancer cells is required for the induction of immunogenic cell death (ICD) by OXA 30 or the combination of CDDP +crizotinib, 20 meaning that cancer cells in which Atg5 expression has been suppressed do not respond to these combination regimens in vivo. 20,30,31 Hence, the fact that HCQ fails to interfere with the efficacy of ICD-based therapeutic regimens might be explained by its incapacity to fully block autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…Intrigued by this observation, we used multiple tests to measure RNA synthesis (and downstream protein synthesis, downstream of RNA transcription) to conclude that most ICD inducers (including anthracyclines, oxaliplatin, lurbinectedin, crizotinib and thiostrepton) actually cause an inhibition of DNA-to-RNA transcription (and hence a subsequent inhibition of RNA-to-protein translation) and that this effect may cause a peculiar ER stress response consisting in the phosphorylation of eIF2α by eIF2α kinase 3 (EIF2AK3, better known as PERK) without any other signs of the unfolded stress response such as activation of the ATF6 and the IRE1-XBP1 axes. 8 10 The aforementioned results suggest that a vast class of ICD inducers (with the exception of microtubular poisons such as vinca alkaloids and taxanes) is able to reduce RNA synthesis, which resembles a response to viral infection. This has two major implications.…”
mentioning
confidence: 99%
“…Based on these insights, we have built medium-throughput high-content screening strategies in which human osteosarcoma U2OS cancer cells are equipped with suitable biosensors (to measure ATP release, calreticulin exposure, type-1 interferon signaling and HMGB1 release), then cultured with compound collections, and characterized for the induction of ICD characteristics, followed by validation experiments in vitro (with other methods and on other cell lines) and in vivo (to measure the effective induction of anticancer immune responses in mouse models). 7 , 8 Several large screens including the measurement of additional stress responses (like all arms of the ER stress response) led to the generation of a data bank, instructing us on the facts that (i) induction of other types of ER stress than eIF2α phosphorylation was not activated upon ICD induction and (ii) that anticancer drugs must have a specific set of physicochemical characteristics that define their propensity to induce ICD, allowing to use artificial intelligence to create a mathematical model, which, based on molecular descriptors, yield a theoretical ‘ICD score’. 5 When computing this ICD score to a library of 50,000 agents, we found that one of the top hits was dactinomycin (DACT, best known as actinomycin D), an agent that has been used by myriads of molecular biologists to inhibit transcription but that is also employed for the chemotherapy of sarcomas.…”
mentioning
confidence: 99%
“…Rat adrenal gland PC12 cells stably expressing doxycyclineinducible Q74-GFP were cultured in Roswell Park Memorial Institute (RPMI)-1640 containing 5% fetal bovine serum and 10% horse serum 82 . Human neuroglioma H4 cells, human osteosarcoma U2OS cells, MCA205 murine fibrosarcoma, and all the other cells were maintained in Dulbecco's modified Eagle's medium (DMEM), supplemented with 10% (v/v) fetal bovine serum (FBS), 10 U mL −1 penicillin sodium and 10 μg mL −1 streptomycin sulfate at 37°C in a humidified atmosphere with 5% CO 2 .…”
Section: Cell Culture and Chemicalsmentioning
confidence: 99%